1990
DOI: 10.1111/j.1365-2273.1990.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral cavity. A review of 176 cases with application of malignancy grading and DNA measurements

Abstract: This retrospective study comprised 176 patients with squamous cell carcinoma of the oral cavity treated at The Linköping University Hospital over a 19-year period. Clinical parameters, microscopic malignancy grading (according to Jakobsson et al. and Glanz and Eichhorn), DNA cytofluorometry, analysis of therapeutic modalities and statistics regarding survival and prognosis are reported. The mean age was 70 years with a male: female ratio of 1.3:1 One hundred and four patients had T1 or T2 tumours and 109 an N0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 96 publications
3
19
0
Order By: Relevance
“…Ploidy failed to predict recurrence (two studies) and response to radiation (two studies). Studies conducted after these reviews are presented in Table 5 [93][94][95][96][97][98][99][100][101][102][103]. These studies generally support the conclusion of the Stell review that nondiploid tumors are associated with poor overall survival.…”
Section: Dna Ploidysupporting
confidence: 51%
See 1 more Smart Citation
“…Ploidy failed to predict recurrence (two studies) and response to radiation (two studies). Studies conducted after these reviews are presented in Table 5 [93][94][95][96][97][98][99][100][101][102][103]. These studies generally support the conclusion of the Stell review that nondiploid tumors are associated with poor overall survival.…”
Section: Dna Ploidysupporting
confidence: 51%
“…The relative importance of aneuploidy in these studies is still unclear, however, because only Westerbeek et al [98] found aneuploidy to be a significant independent predictor of radioresistance in multivariate analysis. In contrast, a significant relationship between diploidy and radioresistance was reported by Tytor et al [93] in T1-4N0-2 oral SCC and by Toffoli et al [100] in T1-2N0 laryngeal SCC. At present, it is difficult to determine from the available literature the relationship between DNA ploidy and response to radiation.…”
Section: Dna Ploidymentioning
confidence: 73%
“…This finding is in contradiction to other published reports where the correlation was usually positive or there was no correlation. In general, a positive correlation with N-stage has been observed in the analysis of other factors reflecting cell proliferative properties, such as Ki67 and DNA analysis [5,12,28,31]. The reverse tendency of N-stage and PCNA in our study may be explained by a specific inclusion criteria our study population.…”
Section: Discussionmentioning
confidence: 39%
“…Kearsly et al 32 reported similar findings comprising mostly oral cavity tumors treated by radiotherapy and/or surgery. A better prognosis in diploidy was also described by Tytor et al 31 for oral cavity tumors treated by surgery and/or radiotherapy and by Kokal et al 33 in mostly tumors of the oral cavity and larynx and treated by surgery and/or radiotherapy. These findings were confirmed, by univariate analysis, in some smaller studies on laryngeal tumors treated either by radiotherapy alone 34,37,38 or treated by surgery and/or radiotherapy with or without chemotherapy.…”
Section: Discussionmentioning
confidence: 81%